Evidence-based policymaking : insights from policy-minded researchers and research-minded policymakers - Bogenschneider, Karen (Routledge, 2010)
This book examines ways to enhance evidence-based policymaking, striking a balance between theory and practice. The attention to theory builds a greater understanding of why miscommunication and mistrust occur. Until we better appreciate the forces that divide researchers and policymakers, we cannot effectively construct strategies for bringing them together.